2023
DOI: 10.3389/fpsyg.2023.1225790
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an environmental enrichment intervention for endometriosis: a pilot study

Grace De Hoyos,
Darlenne Ramos-Sostre,
Annelyn Torres-Reverón
et al.

Abstract: IntroductionWe have previously shown that Environmental Enrichment (EE), a multi-modal psychosocial intervention consisting of increased social interaction, novelty, and open spaces, improved disease presentation, anxiety, and immune-related disturbances in the rat model of endometriosis. However, there is a knowledge gap regarding the effects of EE interventions in patients with this painful, inflammatory chronic disease.AimTo adapt and test the efficacy of an EE intervention on pelvic pain, mental health, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
2
2
0
Order By: Relevance
“…40.52% of MFPP patients had been categorized as “extreme catastrophizing” in our study, which was similar to the results of previous studies conducted among women with endometriosis in 2022 (40.74%), and women with chronic pelvic pain in 2015 (44.02%) [ 9 , 28 ]. Despite the potential bidirectional link between pain and pain catastrophizing, a review of the basic neuroscience processes of pain suggests the stronger effect is pain predicting pain catastrophizing in clinical diagnostic pain conditions that were different from “psychogenic pain”, the direction tested in and supported by the current study [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…40.52% of MFPP patients had been categorized as “extreme catastrophizing” in our study, which was similar to the results of previous studies conducted among women with endometriosis in 2022 (40.74%), and women with chronic pelvic pain in 2015 (44.02%) [ 9 , 28 ]. Despite the potential bidirectional link between pain and pain catastrophizing, a review of the basic neuroscience processes of pain suggests the stronger effect is pain predicting pain catastrophizing in clinical diagnostic pain conditions that were different from “psychogenic pain”, the direction tested in and supported by the current study [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…In line with the previous researches [6,26,27], this study findings reveal that pain catastrophizing showed strong and consistently significant influential role in the association between pain and daily interference, while kinesiophobia and self-efficacy have no independently mediating effect. 40.52% of MFPP patients had been categorized as "extreme catastrophizing" in our study, which was similar to the results of previous studies conducted among women with endometriosis in 2022 (40.74%), and women with chronic pelvic pain in 2015 (44.02%) [9,28]. Despite the potential bidirectional link between pain and pain catastrophizing, a review of the basic neuroscience processes of pain suggests the stronger effect is pain predicting pain catastrophizing in clinical diagnostic pain conditions that were different from "psychogenic pain", the direction tested in and supported by the current study [29].…”
Section: Mediation Effect Of Pain Catastrophizingsupporting
confidence: 89%
“…On the other hand, there are already validated psychometric tools that can be utilized for evaluating the effects of EE in daily human life, such as the Florida Cognitive Activities Scale (FCAS), the Multidimensional Social Integration in Later Life Scale (SILLS), and the International Physical Activity Questionnaire (IPAQ) ( Flores-Ramos et al, 2022 ), along with the Generalized Anxiety Disorder 7 (GAD-7) inventory ( De Hoyos et al, 2023 ). Notably, these psychometric studies have measured cognitive, social, and physical activities, but not the spatial complexity of life environments ( Flores-Ramos et al, 2022 ), further underscoring the gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, these psychometric studies have measured cognitive, social, and physical activities, but not the spatial complexity of life environments ( Flores-Ramos et al, 2022 ), further underscoring the gap in the literature. Other studies have concentrated on social support, novelty, and open spaces as correlates of anxiety in patients with endometriosis and other inflammatory, painful disorders ( De Hoyos et al, 2023 ; Nieves-Vázquez et al, 2023 ), validating the use of GAD-7 while focusing on a different scope of EE. The National Center for Health Statistics (NCHS) in the United States employed a shorter version of the GAD-7, the GAD-2, along with the short form of the Patient Health Questionnaire (PHQ-2), to explore depression symptoms during the COVID-19 lockdown.…”
Section: Introductionmentioning
confidence: 99%